PENGEMBANGAN WISATA BERBASIS PERSEPSI PEGUNJUNG DI KAMPUNG AGROWISATA SENI BUDAYA PASANGGRAHAN UJUNG BERUNG, KOTA BANDUNG - Nurlena; Musadad; Suryana H Achmad (Institut Pariwisata dan Bisnis Internasional, 2019)
Pasanggrahan Art and Cultural Village is a village-based agritourism combining natural tourism with cultural tourism, especially Sundanese culture. The agritourism, located in Ciporeat Hamlet, Pasanggrahan Village, is included in the Bandung City Culture and Tourism Office’s 2018-2023 Strategic Plan, meaning that this tourist destination is already in the local government's development plan. Therefore, this study aims to offer alternatives to the development of agritourism based on the visitor perceptions in order to offer a development concept to the related stakeholders. The data was collected through distributing questionnaires to 50 respondents and conducting interviews with the residents and those who understood the agritourism. The analysis results indicate that the visitors’ bad perception clearly lies in the diversity of tourist attractions, souvenirs, places to eat, and roads within the destination. Therefore, this study focuses the alternative formulations or development efforts on the aspects of what to see, what to buy, what to do, what to arrive, dan what to stay.